Food consumption expenditure of elderly people´s household: an analysis of the national survey of income and expenditure, INEC 2013 - Araya Quesada, Yorleny (2018)
The aim was to analyze the influence of socioeconomic characteristics on foodexpenditure in Costa Rican households that have at least one adult older than 65 yearsold. For this study the results of the National Household Income and ExpenditureSurvey 2013, of “Instituto Nacional de Estadística y Censos”, was used. The influenceof the income, the schooling of the head´s household, the area and the family type onthe consumption expenditure in food, as well as the relation between the area andschooling with the income was studied. It was found that food expenditure was lower inlower income households, that represents major percentage of income. The area andschooling are related to income. In older adult´s households food expenditure is higherthan families with older and young people.